The Cathodic Breakdown Test to Assess Chromic Acid Anodized Aluminum Alloys Corrosion Protection Performance, in Correlation with Salt Spray (Fog) Testing. (10th April 2012) - Ouaziz, Ghita; Savadogo, Oumarou
Abstract : The corrosion protection performance of chromic acid anodized (CAA) coating, applied on aerospace aluminum sheets is determined by the Cathodic Breakdown Test (CBT). The results were compared to those obtained with the classical salt spray test using the standard ASTM B117. A clear experimental procedure was developed to describe this non-standardized test, leading to the conclusion that the CBT results correlate well with those of the salt spray tests. All the sealed samples, which fail in CBT test, also fail in salt spray. The CBT was not identified as a useful tool to differentiate different types of unsealed aluminum bare samples. The CBT failure criteria set was successfully used in the identification of sealed sample failures from salt spray tests. The sealing performance of the sample was correlated to the CBT test parameters. The CBT test lasted at least 2000 times less long than the salt spray test. Furthermore the utilization of a relevant experimental procedure of the CBT testing method is an interesting way to lower significantly the testing time of the evaluation of corrosion protection performance of sensitive coated aerospace materials in comparison to the salt spray method.